Evaluating crop growth between hydroponics and aquaponics with different light inputs - Heo, Jeongwook; Baek, Jeonghyun; Subah, Zarin; Ryu, Jae Hyeon (Frontiers in Horticulture, 2024)
Indoor farming technologies, such as aquaponics and hydroponics, are crucial for advancing sustainable agriculture, especially in urban areas with limited land for conventional agriculture. As there are limited studies conducted to compare these two systems, this study explores the cultivation of five leafy vegetables -1) white leaf beets (Beta vulgaris var. circla), 2) hooker chives (Al-lium hookeri), 3) basils (Ocimum basilicum), 4) lemon balm (Melissa officinalis), and 5) spearmint (Mentha spicata) -in an indoor greenhouse facility using two different food production platforms, an aquaponics system (AS) with catfish (Silurus asotus) and a conventional hydroponics system (HS). The result shows that the plant growth in AS outperforms that in HS, while general growth patterns are significantly affected by the different light sources in AS. Additionally, leaf yield for herbal plants (basil and lemon balm) in AS was 60 -70% more than that in HS. Leaf growth in hooker chives in AS also shows significant improvement (200%) compared to that in HS. It appears that the nutrient sources provided by fish were remarkable, as the average concentration (64 mg/L) of NO3-N was easily achieved in AS. The proposed AS, therefore, would be a promising alternative to produce and supply supplement organic food, ultimately contributing to promoting sustainable agriculture in a changing climate.